What is the Difference? Pragmatic Formalization of Meaning - Surov, I. A. (Scientific and technical information processing, 2024)
The agenda of the information age requests development of a metrologically sound theory of meaning, reflecting its real function in human life. This work aims to meet the challenge. First, the paper analyzes premises of classical and applied semiotics, preventing its mathematical formalization. The most unfortunate of them is objectification of meaning, implying the possibility for its modeling based on set calculus. This approach is shown to contradict the pragmatic, creative and subjectively-contextual nature of natural cognition. After Bateson’s famous dictum, the problem is solved by grounding meaning in the quantum of subjective behavior—the simplest binary decision. Fragments of the corresponding semantic structure are identified in basic models of emotion, cognitive semantics, functional semiotics, and quantum information science. Alignment of these fragments is shown to reproduce the qubit model of meaningful decision-making based on quantum theory. Integrative potential of the presented approach enables productive interaction of psychology, cybernetics, behavioral modeling, artificial intelligence, and quantitative semiotics.